A interiorização da Educação Básica na Bahia: o direito à educação na cidade de Feira de Santana nas décadas de 1960 - 1970 - Dias , Jaqueline Loiola (2024)
The present work entitled “The Internalization of Basic Education in Bahia: The Right to Education in the city of Feira de Santana in the 1960s-1970s” is a master's thesis research that has as its object of study the right to education and the policies of education for basic education in the city of Feira de Santana in the 1960s and 1970s. We seek to highlight local specificities and their articulation with broader social policies in the educational field in Bahia, in Feira de Santana. This study starts from the organization of national public education, analyzes the historical political process regarding the development of national education policies, and culminates in the debate on the right to education as a social right for all. In view of this, the studies were carried out with the following research question: What are the repercussions of the Law of Guidelines and Bases of National Education No. 4,024/1961 in relation to the debate on the internalization of education in Feira de Santana, as a social right among the 1960s to 1970s? The general objective is to characterize and analyze the educational policies implemented in favor of the internalization of basic education in Feira de Santana in the 1960s and 1970s, based on the repercussions of the Law of Guidelines and Bases of National Education No. 4,024/1961. The specific objectives are: to analyze the educational legislation of the municipality of Feira de Santana and Bahia regarding the legal scope and the real context experienced in the period between the 1960s and 1970s; and understand the education policies aimed at basic education, implemented in the interior of Feira de Santana in the 1960s and 1970s. The study has a qualitative approach and to achieve the objectives, documentary analysis was used based on Cellard's studies ( 2012), according to the author, to carry out document analysis it is necessary to analyze the social context and the time in which the context of the document was produced, the researcher must maintain criticality in all analysis processes. News published in the Folha do Norte, subsidized in the collection at the Museu Casa do Sertão located in UEFS, newspapers were cataloged to analyze the repercussions of the Law of Guidelines and Bases of National Education (LDB), number 4,024/1961 and its repercussions in favor of the internalization of basic education in Feira de Santana between the 1960s and 1970. The research results indicate that LDB/1961 directly and indirectly occupied journalistic publications, presenting bases for arguments supported by its legal provisions. Based on the analysis of the set of publications published in newspapers, it is possible to point out the existence of actions that aimed to establish the expansion of access to basic education during this period, promoting the debate on the right to education. The study shows that power relations between civil society and political society contribute to the design of current public and social policies. In this sense, the relations between State and Society represented through public bodies and social groups, directly reflect on policies aimed at society.